Education & Community PaDi UMKM Program as a Digital Literacy Effort for MSME Players (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
Digital literacy is a crucial issue for MSME players, lack of understanding in utilizing digital media hampers the ability to compete in the digital era. The focus of this research is to analyze the marketing communication strategy that PaDi UMKM has initiated in increasing digital literacy among MSME players. This research uses a qualitative approach with data collection techniques through in-depth interviews, literature studies and observation of marketing activities at PaDi Talks activities.  The results found that PaDi UMKM succeeded in increasing the digital literacy of MSME players. The Padi Talks activity directly contributes to improving the digital literacy of MSME players. The concept of digitalization elements from JISC directly contributes to the improvement of digital literacy of MSME players. This program creates an ecosystem among MSME players in the form of access to digital resources needed to optimize their marketing and business operations.
Keywords: Digital Literacy; MSMEs; Marketing Communication